Sex differences in presentation, management, and outcomes among patients hospitalized with acute pulmonary embolism - Pribish, Abby M (Vasc Med, 2020)
While the presence of gender disparities in cardiovascular disease have been described, there is a paucity of data regarding the impact of sex in acute pulmonary embolism (PE). We identified all patients admitted to a tertiary care hospital with acute PE between August 1, 2012 through July 1, 2018. We stratified the presenting characteristics, management, and outcomes between women and men. Of the 2031 patients admitted with acute PE, 1081 (53.2%) were women. Women were more likely to present with dyspnea (59.8% vs 52.0%, p < 0.001) and less likely to present with hemoptysis (1.9% vs 4.0%, p = 0.01). Women were older (63.8 ± 17.4 years vs 62.3 ± 15.0 years, p = 0.04), but had lower rates of myocardial infarction, liver disease, smoking history, and prior DVT. PE severity was similar between women and men (massive: 4.9% vs 3.6%; submassive: 43.9% vs 41.8%; p = 0.19), yet women were more likely to present with normal right ventricular size on a surface echocardiogram (63.2% vs 54.8%, p = 0.01). In unadjusted analyses, women were less likely to survive to discharge (92.4% vs 94.7%, p = 0.04), but after adjustment, there was no sex-based survival difference. There were no sex differences in the PE-related diagnostic studies performed, use of advanced therapies, or short-term outcomes, before and after adjustment (p > 0.05 for all). In this large PE cohort from a tertiary care institution, women had different comorbidity profiles and PE presentations compared with men. Despite these differences, there were no sex disparities in PE management or outcomes.